The Role of Archaeological Sites for the Development of Tourism in the Kurdistan Region of Iraq - األسخاو امىساعر امركخِر زيران رشير دان امترادوسخي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Tourism in the Kurdistan Region ,When one thinks of recreational tourism, especially in the summer, moving his attention to the Kurdistan Region of Iraq, Erbil beautiful cities, water fountains and towering mountains and caverns, which tells the story of the Iraqi men since the earliest civilizations The city of Erbil is a geographical area with its distinct character from the rest of the provinces of Iraq, by virtue of its strategic location in the southwestern part of the Kurdistan Region, and the potential of containing the potential and tourism resources natural and human qualify to become a tourist area attractive to various tourist patterns, but the share of the volume of tourism traffic coming To Iraq is still much lower than the potential of tourism, as well as the economic and social return of them is weak, and given the growing interest in tourism as an important axis of the economic and social development in the Kurdistan Region.